Comparative microbiomic analysis of fecal microbiota associated with abdominal fat in ducks - Yangyang Shen; Yuhang Li; Jing Xiao; Jiawei Li; Yongfei Wu; Yan Wu; Hongbo Tang; Xinyan Fang; Lei Wang; Yujie Gong; Hao Chen; Xueming Yan (Poultry Science)
The gut microbiota, which features complex community structures, colonizes the duck intestine and plays a crucial role in metabolism, immune regulation, and meat quality. Gut-microbiota-regulated abdominal fat deposition is a key factor that affects the meat quality of livestock and poultry. We used 16S rDNA and metagenomic sequencing to investigate the microbial community characteristics of 187 fecal samples from 10 Chinese indigenous duck breeds (five breeds for each of the high/low abdominal fat categories). We explored the relationship between fecal microbiota and abdominal fat deposition. The α diversity of the fecal microbiome in high abdominal fat ducks (HAF) was higher than that in low abdominal fat ducks (LAF). The fecal microbiota and function were also significantly different. At the phylum level, Actinobacteria was significantly enriched in HAF, whereas Proteobacteria, Candidatus, Saccharibacteria, and Fusobacteria were abundant in LAF. At the genus level, Lactobacillus, Alistipes, Corynebacterium, and Lachnoclostridium were more abundant in HAF than in LAF. The Streptococcus, Campylobacter, Helicobacter, Enterobacter, Gallibacterium, and Escherichia genera were significantly enriched in LAF. Microbial functional analysis indicated that the HAF fecal microbiota was mainly involved in carbohydrate, nucleotide, lipid, amino acid, terpenoids, polyketides, and xenobiotic metabolism. In addition, bacteria related to signal transduction, cofactor and vitamin metabolism, and infectious disease were enriched in LAF. This study revealed the relationship between gut microbiota and abdominal fat deposition in ducks. Our findings lay a foundation for the abdominal fat deposition mechanism in ducks and provide a reference for Chinese indigenous duck husbandry.